Energy self-supply of large abattoir by sustainable waste utilization based on anaerobic mono-digestion. (1st April 2015) - Ortner, Markus; Wöss, David; Schumergruber, Alexander; Pröll, Tobias; Fuchs, Werner
Graphical abstract: Highlights: Successful implementation of a new waste and energy concept to large size abattoir. 85% of slaughterhouse waste accumulated converted to energy by anaerobic digestion. Coverage of abattoirs' electrical and thermal energy demand between 50% and 60%. Reduction of main energy and disposal cost by 63%. Reduction of greenhouse gas emissions by 79%. Abstract: Abattoirs have a large number of energy intensive processes. Beside energy supply, disposal costs of animal by-products (ABP) are the main relevant cost drivers. In this study, successful implementation of a new waste and energy management system based on anaerobic digestion is described. Several limitations and technical challenges regarding the anaerobic digestion of the protein rich waste material had to be overcome. The most significant problems were process imbalances such as foaming and floatation as well as high accumulation of volatile fatty acids and low biogas yields caused by lack of essential microelements, high ammonia concentrations and fluctuation in operation temperature. Ultimately, 85% of the waste accumulated during the slaughter process is converted into 2700 MW h thermal and 3200 MW h electrical energy in a biogas combined heat and power (CHP) plant. The thermal energy is optimally integrated into the production process by means of a stratified heat buffer. The energy generated by the biogas CHP-plant can cover a significant share of the energy requirement of the abattoir corresponding to 50% of heat and 60% of electric demand, respectively. In terms of annual cost for energy supply and waste disposal a reduction of 63% from 1.4 Mio € to about 0.5 Mio € could be achieved with the new system. The payback period of the whole investment is approximately 9 years. Beside the economic benefits also the positive environmental impact should be highlighted: a 79% reduction of greenhouse gas emissions from 4.5 Mio kg CO2 to 0.9 Mio kg CO2 annually was achieved. The realized concept received the Austrian Energy Globe Award and represents the first anaerobic mono-digestion process of slaughterhouse waste worldwide.